2020
DOI: 10.1177/1527476420918848
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Media Studies in an Age of Datafication

Abstract: We are at a pivotal moment for understanding and deciding what is actually at stake with datafication. In this contribution, I argue for the increasingly important and politicized role of media scholarship to privilege lived experiences and situated practices as a counter to the active neutralization of data-driven systems and their implications. In particular, I argue for the relevance of media studies to emphasize the uses to which technology is put and explore how data practices relate to other social pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Gumbus and Grodzinsky 18 revealed that data capital can result in discrimination and injustice. Dencik 24 pointed out that the application of the concept of data capital in a datadriven system can introduce "inequalities, discriminate or exclude certain groups, or can dehumanise interaction and decision making around contentious and sensitive issues". Prainsack 25 stated that the bad consequences of nudging based on data could outweigh the benefits.…”
Section: Rq6: What Are the Impacts Of Incorporatingmentioning
confidence: 99%
“…Gumbus and Grodzinsky 18 revealed that data capital can result in discrimination and injustice. Dencik 24 pointed out that the application of the concept of data capital in a datadriven system can introduce "inequalities, discriminate or exclude certain groups, or can dehumanise interaction and decision making around contentious and sensitive issues". Prainsack 25 stated that the bad consequences of nudging based on data could outweigh the benefits.…”
Section: Rq6: What Are the Impacts Of Incorporatingmentioning
confidence: 99%
“…However, the exponential development of digital technologies, and with it the growth in surveillance capitalism (Zuboff, 2019) and the datafication of social life (Dencik, 2020), now also forms part of this narrative, where technocracy dominates (Sylvia & Andrejevic, 2016) and surveillance is increasingly automated, accompanied by the displacement of human judgment and social relations (Andrejevic, 2019, 2020). Consequently, as technocratic fixers, experts find themselves caught up in new and innovative modes of governmentality in which centralized forms of bureaucratic management and organizational control are gradually displaced by more technically advanced, organizationally pervasive, and socially ubiquitous surveillance regimes (Kellogg et al, 2020; Visser et al, 2018).…”
Section: Three Narratives On the Crisis Of Expert Authoritymentioning
confidence: 99%
“…This situation also demands innovative methodological approaches which seek to integrate different perspectives in digital ( Dencik, 2020 ). Big data, enabling new approaches to data, represent an alternative ( Grimm et al, 2017 , January; Woo et al, 2020 ) to traditional approaches that analyse quantitative questionnaires obtained in field studies or experimental work.…”
Section: Introductionmentioning
confidence: 99%